Agricultural production and use in Nalanda, India: Crop, homestead, livestock, and fish cultivation and use - Laing, Alison; Kamal, Mustafa; Faisal, Asif Al; Karki, Saral; Druti, Baishakhee Pashari; Nandi, Ravi; Kumar, Neha; Kishore, Avinash; Gathala, Mahesh; Krupnik, Timothy J. (TAFSSA, 2023)
The TAFSSA district food systems assessment aims to provide a reliable, accessible and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management in Bangladesh, India, and Nepal. It is intended to be a multi-year assessment. This data note summarizes data collected in March- April 2023 to describe what smallholder farmers are cultivating and what they do with the farm products produced. It is part of a pack of data notes that, together, provide a holistic picture of the food system in the district. The survey methodology is briefly summarized in the penultimate page of this data note.